How has the Olympic legacy transformed the heart of East London? Understanding socio-economic exclusions and disproportionate COVID-19 impact on minoritised communities through a rights-based perspective - Islam, Farjana (Frontiers in Sports and Active Living, 2023)
This research paper explores the experience of British-Bangladeshi and Black African Caribbean communities living in the areas surrounding London's Olympic Park, in terms of how they are appropriating the legacy-led socio-spatial changes, applying Lefebvre's right to the city perspective. Highlighting the top-down legacy-led regeneration process, the empirical evidence suggests that the games-led regeneration is contributing to an unjust trade-off between pre-existing minoritised ethnic residents and wealthier gentrifiers, ignoring the real needs of the socially and economically disadvantaged ethnic minority communities in East London. The findings provide a further understanding of factors such as housing and health-related inequalities and sub-standard living conditions, which may have contributed to the disproportionate impact of Covid-19 on the Bangladeshi and African Caribbean people living in East London boroughs. Given the scale of the pandemic, the paper argues that a greater understanding of the socio-structural problems and barriers arising out of poverty and deprivation is needed in order to formulate appropriate policy interventions to reduce disproportionate social, economic and health-related impacts on some minoritised communities, which could be achieved through residents' active participation and appropriation at different stages of the legacy-led regeneration process.